A survey of the legal framework governing the water impacts of proposed shale gas extraction in the Karoo - Jeannes, Deon Bruce (Institute of Marine and Environmental Law, 2015)
It is estimated that South Africa has the eighth largest resources of shale gas reserves in the world. It is reported that shale gas extraction can have important benefits which include economic growth, poverty alleviation, carbon emission reduction and most significantly alleviate the current energy shortage. However the proposed extraction of shale gas using hydraulic fracturing requires large amounts of water and many hazardous chemicals which also risks water resource pollution. This can add to water stress and conflict because the Karoo is a semi-arid, water-deficient and drought prone region. Since the extraction thereof is a relatively new technology in South Africa there is a need to determine if the current regulatory and institutional framework in South Africa will be adequate to meet the demands posed by this potentially game-changing enterprise. This minor dissertation outlines the regulatory framework regarding both the water quality and quantity in the shale gas extraction process. It recommends that while there are some regulatory building blocks in place, many gaps exist. It will recommend that an inter-departmental co-operative steering committee is established to address the many overlapping responsibilities and at times contradicting requirements.